Financial markets in Korea - Suh, Young Kyung (Seoul : The Bank of Korea, 2013)
The book provides an overview of the Korean financial market structure, and of recent developments related to the individual markets.
Includes bibliographical references and index.
oif 06/06/14
Loan
Keywords: Financial services industry -- Korea (South).; Finance -- Korea (South); Capital market -- Korea (South) Derivative securities -- Korea (South) Financial institutions -- Korea (South) Monetary policy -- Korea (South); Money market -- Korea (South) Banks and banking -- Korea (South); Korea (South) -- Economic policy -- 1988-